2014
DOI: 10.1016/j.cell.2014.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria from Diverse Habitats Colonize and Compete in the Mouse Gut

Abstract: SUMMARY To study how microbes establish themselves in a mammalian gut environment, we colonized germ-free mice with microbial communities from human, zebrafish and termite guts, human skin and tongue, soil, and estuarine microbial mats. Bacteria from these foreign environments colonized and persisted in the mouse gut; their capacity to metabolize dietary and host carbohydrates, and bile acids, correlated with colonization success. Co-housing mice harboring these xenomicrobiota with one another, with mice harbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
274
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 329 publications
(293 citation statements)
references
References 46 publications
18
274
1
Order By: Relevance
“…Detailed characterization revealed that 'Flintibacter butyricus' can grow on the amino acids glutamine and glutamate (but not leucine, asparagine, lysine, arginine and aspartic acid), producing up to 7 mM butyrate from 20 mM substrate. Moreover, miBC provides the first cultivable member of the 'Muribaculaceae' (family S24-7), which is known to be a dominant bacterial group in the mouse gut 6 . To confirm the latter observation and assess the occurrence of all novel bacteria within miBC, draft genomes were compared to metagenomic species (MGS) 24 from a comprehensive shotgun sequencing study of the mouse gut metagenome 3 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed characterization revealed that 'Flintibacter butyricus' can grow on the amino acids glutamine and glutamate (but not leucine, asparagine, lysine, arginine and aspartic acid), producing up to 7 mM butyrate from 20 mM substrate. Moreover, miBC provides the first cultivable member of the 'Muribaculaceae' (family S24-7), which is known to be a dominant bacterial group in the mouse gut 6 . To confirm the latter observation and assess the occurrence of all novel bacteria within miBC, draft genomes were compared to metagenomic species (MGS) 24 from a comprehensive shotgun sequencing study of the mouse gut metagenome 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Improving the availability of representative isolates from the mouse gut microbiome is essential for future studies using gnotobiotic mice, particularly because the first reference gene catalogue of the mouse gut microbiota shows very limited overlap with human gut microbial gene diversity 3 . Furthermore, the host species from which bacteria originate influences colonization processes and the effects on host physiology [4][5][6] . Hence, concerted actions to archive and describe bacterial isolates in a host-specific fashion together with appropriate genomic databases are urgently needed 7,8 .…”
mentioning
confidence: 99%
“…Therefore, the abnormal microbiota that caused severe colitis in the Atg7 cKO mice may have different properties than the microbiota that were found in previous studies. Seedorf et al (61) reported that bacteria from diverse habitats can colonize in the germfree mouse gut after cohousing. However, in that report, several bacterial groups, such as the soil-derived bacteria, dominated even in the presence of other bacterial communities, whereas some other bacteria could not be easily transmitted from one animal to another animal with an established bacterial community.…”
Section: Discussionmentioning
confidence: 99%
“…For specialization, a host-microbe pair should display a direct preferential relationship in addition to any phylogenetic correlation. Perhaps the most straightforward method of testing this is through transplantation experiments, whereby cultured strains (or entire gut communities 21 ) are introduced into gnotobiotic animals, and the microbial colonization load recorded as a proxy for host-microbe compatibility.…”
Section: The Specialized Gut Symbionts Of Beesmentioning
confidence: 99%
“…In a competition between a specialized community and an artificially introduced one, however, the one that has evolved to thrive in the gut of that particular host species will almost invariably win out. 21 There are myriad reasons why we should care about host specialization. From a practical standpoint, specialized gut communities are indicative of intimate, evolved interactions between host and microbe, and hence are key to mediating symbiotic benefits that affect host biology.…”
mentioning
confidence: 99%